The Challenges of Corrupt Practices and Its implication on Good Governance in Nigeria - Adedeji, Amos (Journal of Techno-Social, 2025)
Corruption is one of the biggest obstacles to economic and political advancement of Nigeria. This phenomenon has grown into a cankerworm that is deeply ingrained in our system's architecture.  The broad objective of this study is to examine the challenges of corrupt practices and its implication on good governance in Nigeria. Leadership theory was employed as the theoretical framework of the paper. The study adopted mixed methods to collecting data. The findings identified bad leadership, lack of adequate funding of anti-corruption agencies, lack of reforms, lack of national integration and poor working conditions as catalysts of corruption in Nigeria. The study recommended formulation and implementation of policies that promote good governance, independent of anti-corruption agencies and demonstration of statutory power to prosecute corrupt persons without considering their status, to serve as deterrence. It is appropriate to start a more fruitful mass citizen mobilization for national integration in order to instill a sense of patriotism in the populace.